Current Issues in Thai Criminal Justice - Janekarn, Chavanut (วารสารกระบวนการยุติธรรม, 2012)
This paper provides and overview of recent crime trends and criminal justice issues in Thailand, based on crime reports between 2002 and 2011, Thai National Crime Victimization Surveys, and relevant statistic and resources from core criminal justice agencies. Through analysis and review of these reports, many interesting findings and trends concerning crime and criminal justice in Thailand were revealed, such as: a decrease in violent and property crime since 2006: a sharp rise in the number of drug offenses; a decrease in the number of offenses reelated to distribution of illegal obscene publications following decreiminalization of adult media; a significant decrease in the number of arrested youth offenders after the new measures to protect youth from unlawaful areest or detention were applited; a high dark figure of crime; a higher rate of crime in urban areas; and a high number of remanded suspects awaiting trial. Taking these issues into consideration, this paper also provides recommendations for further improvement of criminal justice policies concerning crime prevention and the treatment of offenders.